Pseudophylline bushcrickets from Pahang in the repository of the natural history museum, London and Zoologisches Museum Hamburg, Germany (Orthoptera: Tettigoniidae: Pseudophyllinae) / M Muzamil - M., Muzamil (Universiti Teknologi MARA Cawangan Pahang, 2005)
The Pseudophylline bushcrickets from Pahang which are reposited in Natural History Museum, London and Zoologisches Museum Hamburg, Germany are represented. A total of 5 species under 5 genera were recorded from Pahang, Malaysia. The species were Cratioma oculatum Karny, Pseudophyllus hercules (Kamy), Onomarchus cretaceus (Serville), Morsimus quadratus quadratus (Rehn) and Typhoptera quadrituberculata (Westwood).